Corporate governance a synthesis of theory, research, and practice - Anderson, Ronald; Baker, H. Kent (Harold Kent) 1944- (Hoboken, New Jersey Wiley, 2010)
"A detailed look at the importance of corporate governance in today's business world. The importance of corporate governance became dramatically clear at the beginning of the twenty-first century as a series of corporate meltdowns from managerial fraud, misconduct, and negligence caused a massive loss of shareholder wealth. As part of the Robert W. Kolb Series in Finance, this book provides a comprehensive view of the shareholder-manager relationship and examines the current state of governance mechanisms in mitigating the principal-agent conflict. This book also offers informed suggestions and predictions about the future direction of corporate governance. Relies on recent research findings to provide guidance through the maze of theories and concepts. Uses a structured approach to put corporate governance in perspective. Addresses essential issues related to corporate governance including the idea of principal-agent conflict, role of the board of directors, executive compensation, corporate monitoring, proxy contests and corporate takeovers, and regulatory intervention"--
Content; PART I: Background and Perspectives on Corporate Governance; 1: An Overview of Corporate Governance; 2: The Financial Determinants of American Corporate Governance: A Brief History; 3: Corporate Governance Systems; 4: Corporate Governance Best Practices; 5: What's Wrong with Corporate Governance Best Practices; 6: The Effect of Corporate Governance on Performance; 7: International Corporate Governance Research; 8: Agency Theory: Incomplete Contracting and Ownership Structure; 9: Theories and Models of Corporate Governance; 10: Unfettered Agents?: The Role of Ethics in Corporate Governance; PART II: Internal Governance; 11: Board Composition and Organization Issues; 12: Board Diversity; 13: Board Subcommittees for Corporate Governance; 14: Executive Compensation: Incentives and Externalities; 15: Compensation Consultants and Executive Pay; 16: Corporate Governance and Ownership Structure; 17: The Effects of Management Turnover on Firm Performance; PART III: External Governance; 18: Corporate Monitoring by Blockholders; 19: The Governance of Family Firms; 20: Institutional and Other Shareholders; 21: The Politics of Shareholder Activisim; 22: Executive Behavior: A Creditor Perspective on Managerial Ownership; 23: Governance of Banking Institutions; 24: Corporate Governance: Nonequity Stakeholders; 25: Proxy Contests; 26: Corporate Takeovers and Restructurings; 27: Corporate Takeovers and Wealth Creation; 28: Corporate Governance and Accountability; 29: Corporate Governance Rules and Guidelines; 30: Economics Aspects of Corporate Governance and Regulation; PART IV: Answers to Chapter Discussion Questions; Index
UP System perpetual contents
Includes index
Keywords: Corporate governance; Industrial management